Osteoporosis Screening Disparities among Ethnic and Racial Minorities: A Systematic Review - Anoush Calikyan; Jillian Silverberg; Katherine M. McLeod (Journal of Osteoporosis)
Background. Osteoporosis is a preventable disease that is simple and cost-effective to screen based on clinical practice guidelines, yet many patients go undiagnosed and untreated leading to increased burden of the disease. Specifically, racial and ethnic minorities have lower rates of dual energy absorptiometry (DXA) screening. Inadequate screening may lead to an increased risk of fracture, higher health care costs, and increased morbidity and mortality disproportionately experienced by racial-ethnic minority populations. Purpose. This systematic review assessed and summarized the racial and ethnic disparities that exist for osteoporosis screening by DXA. Methods. Using terms related to osteoporosis, racial and ethnic minorities, and DXA, an electronic search of databases was performed in SCOPUS, CINAHL, and PubMed. Articles were screened using predefined inclusion and exclusion criteria which dictated the final articles used in the review. Full text articles that were selected for inclusion underwent quality appraisal and data extraction. Once extracted, data from the articles were combined at an aggregate level. Results. The search identified 412 articles. After screening, a total of 16 studies were included in the final review. The overall quality of the studies included was high. Of the 16 articles reviewed, 14 identified significant disparities between racial minority and majority groups and determined that the eligible patients in racial minority groups were less likely to be referred to DXA screening. Conclusion. There is a significant disparity in osteoporosis screening among racial and ethnic minorities. Future efforts should focus on addressing these inconsistencies in screening and removing bias from the healthcare system. Additional research is required to determine the consequence of this discrepancy in screening and methods of equitizing osteoporosis care.